Islamic values for children - Assiff-Tarabain, Lila; Gurmeet (Goodword Books New Delhi, 2009)
Islamic Values for Children from the Goodword series introduces young readers to key moral and ethical principles in Islam, such as honesty, kindness, and respect. Through simple stories and lessons, it aims to instill a strong foundation of Islamic values in an easy-to-understand and engaging way for children.